Simultaneous incisional hernioplasty and abdominoplasty as effective and safe surgical methods - Adolfo Rafael Jaén Oropeza; José Miguel Gonzalo Goderich Lalán; Miguel Ángel Quevedo Tamayo; Rider Díaz Pérez; Alexander Rosell Fernández (Centro Provincial de Información de Ciencias Médicas, 2017)
Introduction: simultaneous hernioplasty-abdominoplasty provoque favorable clinic-cosmetic results in patients with excess skin and adipose tissue in the lower abdomen. Objective: to evaluate the results of these surgical methods. Method: a prospective study of 16 operated patients with incisional hernia and pendulum abdomen was carried out in "Dr. Juan Bruno Zayas Alfonso"UniversityGeneralHospital inSantiago de Cuba, during 2015-2016. Results: There was a prevalence of the imphraumbilical hernia, 10-15 cm ring, dermolipectomy and Rives technique, as well as seroma as postoperative complication. The mean age was 40 years; antimicrobian and antithrombotic prophylaxis were carried out. The polypropylene prosthesis was used in 100% of the affected patients. Conclusion: eventroplasty and abdominoplasty are safe and effective methods in patients adequately selected.